The caretaker : a novel - Kliewer, Marcus (Atria ; 12:01 / Atria, 2026)
"Marcus Kliewer, the debut author of horror phenom, WE USED TO LIVE HERE, returns with a new dark tale about the perils of accepting a job through Craigslist"-- Provided by publisher.